Cisco Integration of Innovation and Operation - Dong, Xiaoying; Yu, Yan.; Zhou, Jiali (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book picks Cisco as an example to propose a framework of ambidextrous integration of innovation and operation, which is the key to the success of global companies along their evolutions, especially for those technology companies. The authors try to find how the company combines active innovation and efficient operation for its sustainable development. On the basis of comprehensive analysis of the strategic leadership, change management, innovation system, M&As, IT-enabled value chains, collaboration, etc., in Cisco, as well as the interviews with Cisco staff, this book shows that management practices shape the balance of internal-external resources for explorative-exploitative innovations. IT strategies and implementation enable efficient operations when innovations are identified and justified in the leading company. Managerial insights for sustainable competitiveness can be gained from Cisco practices in this book. The companion of the book, Huawei: From Catching up to Lead, telling another growth path of technology company in China by similar framework.
Chapter 1 Integration of innovation and operation: The way multinational companies survive -- Chapter 2 Strategic leadership -- Chapter 3 Enterprise transformation and change management -- Chapter 4 Innovation system -- Chapter 5 M&A strategy and management -- Chapter 6 Strategic alliance and Partnership management -- Chapter 7 Build highly adaptable corporate culture -- Chapter 8 Corporate Governance and Risk Management -- Chapter 9 Informatization and value chain management -- Chapter 10 Collaborative organization and knowledge management -- Appendix.
Keywords: Entrepreneurship; New business enterprises; Management; Business information services; Entrepreneurship; Management; IT in Business